PERAMALAN VOLATILITAS RETURN NILAI TUKAR RUPIAH TERHADAP US DOLLAR MENGGUNAKAN METODE EGARCH, TGARCH, DAN APARCH - KARANA, MADE NONIK PRAMESTI; SUMARJAYA, I WAYAN; SARI, KARTIKA (E-Jurnal Matematika; Vol 13 No 1 (2024), 2024)
Exchange rates play a crucial role among macroeconomic variables, exerting a significant influence on a country's economic landscape. Fluctuations in these rates can impact a nation's stability and economic activities. Consequently, it becomes essential to engage in forecasting endeavors, particularly in predicting the exchange rate of the rupiah against foreign currencies, with a focus on the US dollar. Certain instances in financial data reveal an asymmetric volatility response, often referred to as the leverage effect. To address this challenge, asymmetric GARCH models, including EGARCH, TGARCH, and APARCH, prove instrumental. This research endeavors to identify the most effective model among EGARCH, TGARCH, and APARCH using data pertaining to the rupiah's exchange rate against the US Dollar from March 2, 2020, to June 2, 2022. The findings indicate that the APARCH (1,2) model stands out as the optimal choice for predicting volatility, boasting the smallest AIC value in comparison to its counterparts. As per the research outcomes, volatility witnessed a decline from the initial day to the fourteenth day.